Mirando a Futuro el Rol de la Mujer Latinoamericana como Peacekeepers - Lodeiro Encina, Andrea (Hemisferio - Revista del Colegio Interamericano de Defensa, 2017)
Despite the repeated calls by the UN Security Council to increase the percentage of women in peacekeeping operations, the participation of Latin American women as peacekeepers in 2017, is still insignificant in ground operations especially among military observer. The author raises significant doubts about whether Latin American countries in the future will be able to contribute female peacekeeping contingents and discusses the factors that could increase the role of women in peacekeeping operations within a reasonable timeframe. In this regard, the analysis discusses the reasons attributed to such a low number of Latin American women serving as peacekeepers, and then goes on to identify some approaches that could increase their role as relevant peacebuilders.